Protective effect of curcumin on immune system and body weight gain on rats intoxicated with 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) - Ciftci, Osman; Tanyildizi, Sadettin; Godekmerdan, Ahmet (Taylor & Francis Inc, 2010)
Material and methods: For this purpose, 128 3-4-month-old Wistar albino rats with 280-310 g body weights were used. The 2 mu g/kg dose of 2,3,7,8-TCDD and 100 mg/kg dose of curcumin were dissolved in corn oil and orally given to the rats found in the experimental and control groups. Then, the serum samples were taken from all rats at 15, 30, 45 and 60 days to analyzed for the determination of TNF-alpha, IFN-gamma, IL-12 and IL-13 levels by ELISA method. The data of body weight gain was measured at 15, 30, 45 and 60 days. Results: The results indicated that 2,3,7,8-TCDD caused a significant increase (p < 0.05) in serum TNF-alpha level. However, it caused significant (p < 0.05) decreases in the levels of IFN-gamma, IL-12 and IL-13 in rats. On the contrary, curcumin increased IFN-gamma, IL-12 and IL-13 levels, but decreased TNF-alpha level in rats. Additionally, TCDD caused significant (P < 0.01) reductions in the body weight gain. However, curcumin reversed this effect of TCDD. Conclusion: 2,3,7,8-TCDD significantly suppressed the humoral immunity and body weight gain in rats at doses of 2 mu g/kg. However curcumin, which was found in some plants, eliminated the effect of TCDD on immune system and body weight when it was given together with 2,3,7,8-TCDD. It is thought that this effect may have occurred via curcumin and TCDD binding aryl hydrocarbon receptor (AhR) competitively.
Keywords: 2,3,7,8-TCDD; curcumin; cytokine; body weight